Kidney Expression of Toll Like Receptors in Lupus Nephritis: Quantification and Clinicopathological Correlations - Fabrizio Conti; Francesca Romana Spinelli; Simona Truglia; Francesca Miranda; Cristiano Alessandri; Fulvia Ceccarelli; Michele Bombardieri; Konstantinos Giannakakis; Guido Valesini (Mediators of Inflammation)
Objective. The study aimed at locating and quantifying Toll Like Receptor (TLR) 3, 7, 8, and 9 expression in kidney of patients with lupus nephritis (LN) and correlating them with clinicopathological features. Methods. Kidney sections from 26 LN patients and 4 controls were analyzed by immunohistochemistry using anti-human TLR3, TLR7, TLR8, and TLR9 polyclonal antibodies; the number of TLR-positive nuclei/mm2 was evaluated on digitalized images. Results. Compared to controls, LN showed a significantly higher amount of glomerular and tubulointerstitial TLR9 (p=0.003 and p=0.007), whole and tubulointerstitial TLR3 (p=0.026 and p=0.031), and a higher tubulointerstitial TLR7 (p=0.022). TLR9 positively correlated with activity index (p=0.0063) and tubular TLR7 with chronicity index (p=0.026). TLR9 positively correlated with Renal-SLEDAI (p=0.01). Conclusions. This is the first study quantifying kidney expressions of TLRs in LN patients; the results show an overexpression of TLR3, TLR7, and TLR9 and demonstrate a correlation with clinicopathological indices supporting a role of these mediators in the pathogenesis of LN.